2020
DOI: 10.1002/nbm.4311
|View full text |Cite
|
Sign up to set email alerts
|

BOLD fMRI and hemodynamic responses to somatosensory stimulation in anesthetized mice: spontaneous breathing vs. mechanical ventilation

Abstract: Mouse functional MRI (fMRI) has been of great interest due to the abundance of transgenic models. Due to a mouse's small size, spontaneous breathing has often been used. Because the vascular physiology affecting fMRI might not be controlled normally, its effects on functional responses were investigated with optical intrinsic signal (OIS) imaging and 9.4 T BOLD fMRI. Three conditions were tested in C57BL/6 mice: spontaneous breathing under ketamine and xylazine anesthesia (KX), mechanical ventilation under KX,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…Each mouse with trimmed whiskers was placed in a customized cradle with earplugs and a bite bar. To maintain anesthesia during the scan, supplementary doses (25 mg/kg ketamine and 1.25 mg/kg xylazine) were infused intermittently (every 30 or 45 minutes) through an IP line, as deemed necessary based on changes in physiological parameters (Jung et al, 2019; Shim et al, 2018; Shim et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each mouse with trimmed whiskers was placed in a customized cradle with earplugs and a bite bar. To maintain anesthesia during the scan, supplementary doses (25 mg/kg ketamine and 1.25 mg/kg xylazine) were infused intermittently (every 30 or 45 minutes) through an IP line, as deemed necessary based on changes in physiological parameters (Jung et al, 2019; Shim et al, 2018; Shim et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…However, the results of such studies have been inconsistent, and bilateral activity caused by cardiovascular responses has frequently been reported (Reimann et al, 2018) when only the contralateral hemisphere was expected to be active. Recently, we found that ketamine/xylazine anesthesia produces reliable localized somatosensory-induced fMRI responses (Jung, Shim, & Kim, 2019; Shim et al, 2018; Shim, Lee, & Kim, 2020) without changing the cardiac pulsations or respiration rate (Shim et al, 2018). Thus, we used ketamine/xylazine anesthesia for this mouse fMRI study to characterize the BOLD fMRI responses to visual stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study (published after the date the systematic search was performed) in mechanically ventilated vs. spontaneously breathing mice measured vessel diameter with optic intrinsic signal imaging as well as BOLD response to electrical paw stimulation. At the average p a CO 2 of 83 mmHg in spontaneously breathing animals, baseline vessel diameter was significantly larger, and increase in vessel diameter as well as the peak BOLD response to paw stimulation were significantly reduced and delayed compared to values measured at an average p a CO 2 of 41 in mechanically ventilated animals (Shim et al, 2020). One of the included interventional studies however observed a significant decrease of response to stimulation already with 1% CO 2 admixture, corresponding to an increase in p a CO 2 of 5 mmHg (Nasrallah et al, 2015).…”
Section: Changes In P a Comentioning
confidence: 69%
“…While both routes may be used in terminal studies, the less invasive oropharyngeal route should be chosen for recovery studies. While rats appear to recover with few complications from oropharyngeal intubation (Rivard et al, 2006), a recent publication described cessation of weight gain in the first week after extubation in mice (Shim et al, 2020). One of the authors (AS) has however successfully recovered mice after intubation and mechanical ventilation, suggesting that longitudinal studies with appropriate ventilatory management are feasible in mice, although the technical challenges may require an experienced operator.…”
Section: Blood Oxygenation and Ventilationmentioning
confidence: 99%
“…However, isoflurane may not be the ideal agent. It has strong vasodilatory effects resulting in slower and weaker hemodynamic responses to stimulation [ 144 ]. Moreover, unspecific bilateral BOLD signal changes in unilateral paw stimulation studies in mice have been reported [ 38 , 122 ], as well as pronounced differences of fc patterns under isoflurane to those found in awake rats [ 121 ].…”
Section: Discussionmentioning
confidence: 99%